La reserva de ley y la seguridad jurídica como mecanismos para tutelar los derechos de la naturaleza: un estudio de las sentencias n.° 32-17-IN/21 y n.° 22-18-IN/21 de la Corte Constitucional del Ecuador (Tema Central) - Koehn, Lena (2022)
The recognition of rights of nature is one of the most innovative aspects of the current Constitution of Ecuador and has attracted the attention of lawyers all over the world. This especially since 2019, when the Constitutional Court of Ecuador began to systematically concretize the abstract constitutional terms and examine the relation between rights of nature and other constitutional rights and guarantees. This paper aims to contribute to the latter by analyzing the constitutional guarantee of compulsory legislative (instead of e.g. administrative) regulation (reserva de ley) and the right to legal certainty and its role in defending rights of nature. After having introduced both constitutional concepts, the article proceeds to examine the Constitutional Court judgements n.° 32-17-IN/21 y n.° 22-18-IN/21 (Mangrove Case) focusing on the guarantee of compulsory legislative regulation (reserva de ley) and legal certainty as means to protect rights of nature. It is shown, that through the discussed constitutional concepts the Constitutional Court of Ecuador has limited the administrative regulation of rights of nature appealing to the responsibility of the legislator in matters of fundamental constitutional relevance, among them, rights of nature. The paper concludes that Constitutional Court of Ecuador thereby not only defends rights of nature but also strengthens participative democracy.